Reduction of dengue incidence in Brazil in 2020: control or sub notification of cases due to COVID-19? (Research, Society and Development, 2020)
Caused by the SARS-CoV-2 virus, the COVID-19 pandemic took its first victims in Brazil still in February 2020. In a short time, the country became one of the most affected by the disease and had already been facing difficulties in the control of other endemics, among them dengue. The social isolation measures adopted to reduce the SARS-CoV-2 infection in the country affected several sectors of assistance, including health. The objective of this study was to analyze the potential impact of the COVID-19 pandemic on actions to control dengue and consequent reduction in notifications in Brazil. This is a descriptive and documentary study, in which epidemiological bulletins published by the Ministry of Health of Brazil and other data available on the websites of the World Health Organization, Pan American Health Organization and the National Council of Health Secretariats were analyzed, referring to the period from 2015 to 2020 in the months of January to August of each year, as well as, official documents such as information note No. 8/2020. The obtained results showed a change in the behavior of dengue in 2020 when compared to previous years, revealing a reduction in the number of notified cases of the disease from the period in which the actions against COVID-19 began. It was concluded that in 2020 there was probably no decrease in the incidence of dengue in Brazil, but rather sub notification of cases, influenced by changes in the dengue control program and inaccessibility to care services.